Leadership development course effectiveness in higher education: a gap analysis / Erlane K Ghani ... [et al.] - K Ghani, Erlane; Mohamed Jais, Ismie Roha; Abdul Manaf, Mohd Mursyiddin (2014)
This study reports the perceptions of individuals currently in the leadership positions within the higher education institutions of Malaysia on the effectiveness of leadership competency development courses provided by AKEPT. Specifically, this study examines five components of leadership competency development namely, idealised attributes, idealised behaviours, intellectual stimulation, inspirational motivation and individualised consideration. Using questionnaire survey on 38 individuals that holds top management in Malaysian public universities, the results show that there is a significant gap in perception of the expected effectiveness of leadership competency development course and the actual effectiveness of leadership competency courses provided by AKEPT. Such findings provide understanding to AKEPT on the leaders’ expectation and guide AKEPT to strategise ways in achieving the goals of transformational leaders among public universities